APLIKASI MOTIF MANUSKRIP PADA BATIK: Pewarisan Budaya melalui Proses Pembelajaran terhadap Mahasiswa ISI Padangpanjang - dini yanuarmi (Studi Budaya Nusantara, 2020)
ABSTRACTThis paper describes the motives found in manuscripts or ancient manuscripts are tangible cultural heritage, which can be categorized as visual culture. Its presence can be seen in plain view and all the time. A noble and monumental cultural heritage, can be threatened by extinction due to human activities and natural disasters. It is fitting for the cultural heritage of the heritage of the past to be preserved and maintained. To maintain the sustainability of these motifs can be revitalized and applied to various media and techniques, such as batik. Batik in the form of one technique in decorating the fabric surface with the application of motifs found in the manuscript. More than that, the existing motives can be developed by creating without changing the original shape. The Craft Art Study Program at the Indonesian Art Institute in Padangpanjang after collaborating with the Regional Literature Study Program of Andalas University, tried to maintain the historical heritage by applying manuscript motifs to batik. The motive that has been applied is the manuscript motif found in the Pakandangan area of Padangpariaman district and Lunang Silaut in the South Coast district. Some works designed by students interested in textiles are made using natural and synthetic coloring. So that batik illumination is born that is creative, innovative and competitive.Tulisan ini memaparkan  tentang motif yang terdapat pada manuskrip atau naskah-naskah kuno merupakan warisan budaya tangible, yang dapat dikategorikan sebagai budaya visual. Kehadirannya dapat dilihat secara kasat mata dan sepanjang waktu. Warisan budaya yang adiluhung dan monumental, dapat terancam kepunahannya dikarenakan ulah manusia dan terjadinya bencana alam.        Sudah sepatutnya warisan budaya tradisi peninggalan masa lampau dijaga dan dipertahankan keberadaannya. Untuk menjaga kelestariannya, motif tersebut dapat direvitalisasi dan diaplikasikan pada berbagai media dan teknik, seperti pada batik. Batik berupa salah satu teknik dalam menghias permukaan kain dengan aplikasi motif yang terdapat pada manuskrip. Lebih dari itu, motif yang ada dapat dikembangkan dengan cara dikreasikan tanpa merubah bentuk aslinya. Program Studi Seni Kriya pada Institut Seni Indonesia Padangpanjang setelah menjalin kerjasama dengan Program Studi Sastra Daerah Universitas Andalas, mencoba menjaga peninggalan sejarah tersebut dengan menerapkan motif-motif manuskrip pada batik. Motif yang sudah diaplikasikan adalah motif manuskrip yang terdapat di daerah Pakandangan kabupaten Padangpariaman dan Lunang Silaut kabupaten Pesisir Selatan. Beberapa karya yang didesain oleh mahasiswa minat tekstil dibuat dengan menggunakan pewarnaan alami dan sintetis. Sehingga lahir batik iluminasi yang kreatif, inovatif dan kompetitif.